Plaosan Temple Ornaments As Iconography Metaphorical Hindu-Buddhist Ideology - Handriyotopo, Handriyotopo (Harmonia: Journal of Arts Research and Education, 2022)
Plaosan Temple is a building structure filled with beautiful ornaments and decorations, reliefs, and statues. Therefore, this research aims to analyze the metaphorical aspect of symbolism in the Plaosan temple reliefs, which represent Hindu and Buddhist ideologies. It also aims to understand the iconographic meaning of this structure as a temple building that unites differences for a peaceful purpose. This is a qualitative descriptive and interpretative research with the “minus one” technique used to determine the effect of removing an element of the temple. The hermeneutic-metaphorical interpretive description was used to visualize the ornaments’ symbols and determine the philosophical meaning between the ideological domain of Hindu symbolism and Buddhism. The results showed that the manifestation of love from the Plaosan temple is indicated in its temple’s relief elements and decorated ornaments.